2014
DOI: 10.1002/hyp.10130
|View full text |Cite
|
Sign up to set email alerts
|

Assessing stand water use in four coastal wetland forests using sapflow techniques: annual estimates, errors and associated uncertainties

Abstract: Abstract:Forests comprise approximately 37% of the terrestrial land surface and influence global water cycling. However, very little attention has been directed towards understanding environmental impacts on stand water use (S) or in identifying rates of S from specific forested wetlands. Here, we use sapflow techniques to address two separate but linked objectives: (1) determine S in four, hydrologically distinctive South Carolina (USA) wetland forests from 2009-2010 and (2) describe potential error, uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In upland closed-canopy forests, transpiration generally far exceeds evaporation (Kool et al, 2014); for examples, evaporation was 8% of ET during the growing season in a closed-canopy forest in the southeastern United States (Wilson et al, 2000) or evaporation averaged 0.19-0.38 mm/day in a temperate coniferous forest (Schaap & Bouten, 1997). If canopy transpiration in the present study was assumed to bẽ 2-3 mm/day, as observed for a reasonably similar ash-sweetgumbaldcypress forest in the south-eastern United States (Krauss et al, 2014), evaporation at our study site would be 22-36% of estimated ET in the growing season months (June-September). This proportion is more consistent with observations in sparser semi-arid (e.g., Baldocchi, Xu, & Kiang, 2004Raz-Yaseef et al, 2010;Scott et al, 2003) or boreal forests with more radiation reaching the forest floor (reviewed by Baldocchi & Ryu, 2011;Iida et al, 2009).…”
Section: Evaporation As Part Of Et: Modelling and Scalingmentioning
confidence: 74%
See 1 more Smart Citation
“…In upland closed-canopy forests, transpiration generally far exceeds evaporation (Kool et al, 2014); for examples, evaporation was 8% of ET during the growing season in a closed-canopy forest in the southeastern United States (Wilson et al, 2000) or evaporation averaged 0.19-0.38 mm/day in a temperate coniferous forest (Schaap & Bouten, 1997). If canopy transpiration in the present study was assumed to bẽ 2-3 mm/day, as observed for a reasonably similar ash-sweetgumbaldcypress forest in the south-eastern United States (Krauss et al, 2014), evaporation at our study site would be 22-36% of estimated ET in the growing season months (June-September). This proportion is more consistent with observations in sparser semi-arid (e.g., Baldocchi, Xu, & Kiang, 2004Raz-Yaseef et al, 2010;Scott et al, 2003) or boreal forests with more radiation reaching the forest floor (reviewed by Baldocchi & Ryu, 2011;Iida et al, 2009).…”
Section: Evaporation As Part Of Et: Modelling and Scalingmentioning
confidence: 74%
“…Although evaporation is often a small component of terrestrial water budgets (Baldocchi & Ryu, 2011), particularly in closed canopy forests, it could be reasoned that wetlands having higher evaporation could result in high total evapotranspiration (ET). Wetland forest structure is highly variable (Allen, Whitsell, & Keim, 2015), so it is difficult to generalize across field studies, but even closed-canopy wetland forests have not been shown to have particularly high transpiration rates (Bosch, Marshall, & Teskey, 2014;Krauss, Duberstein, & Conner, 2014) compared to upland forests in the same region (e.g., Domec et al, 2012). Given heat conduction and storage differences between water and soil, the influence of floodwater on proportional contributions of evaporation versus transpiration may distinguish wetland energy and water budgets from those of upland environments.…”
Section: Introductionmentioning
confidence: 99%
“…High salinity causes osmotic stress and decreased stomatal conductance [126], as indicated by decreased water use efficiency from 100 kg/day on a freshwater site to 23.9 kg/day on a saline water site [127,128]. In tidal forested wetlands, increased soil water salinity negatively reduces nutrient uptake in bald cypress [128][129][130][131][132], which in turn may decrease nitrogen and P burial [133].…”
Section: Treesmentioning
confidence: 99%
“…Such upscaling approaches depend crucially on quadrat surveys (Granier et al, 1996). Although we have done our best to sample representative quadrats within the eddy tower footprint, errors in the quadrat survey and variations in wind direction may cause uncertainties in estimations of stand transpiration using the sap flow method (Köstner et al, 1998;Krauss, Duberstein, et al, 2015). Our calculations of T strictly follow the standard sap flow method; we therefore assume that they are reliable within that context.…”
Section: Estimating Stand Canopy Transpirationmentioning
confidence: 99%